Exploring Kahoot's Potential to Foster Close Reading and Student Engagement - Silvia Sari Setyowati; Atik Rokhayani (Universitas Majalengka, 2026)
The integration of digital learning technologies has become increasingly important in English language education to improve students' reading comprehension and classroom engagement. However, many elementary school students continue to experience difficulties in maintaining attention and actively participating in reading activities, particularly when conventional instructional methods are applied. This study aimed to investigate the potential of Kahoot!-based learning in encouraging close reading and enhancing student engagement during descriptive text learning among sixth-grade elementary school students. A qualitative descriptive approach was employed involving 24 sixth-grade students at Elementary School. Data were collected through classroom observations, semi-structured interviews, and vocabulary reflection sheets. The data were analyzed using the interactive qualitative analysis model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing through triangulation. The findings revealed that Kahoot!-based learning increased students' behavioral, emotional, and cognitive engagement during reading activities. Students actively reread descriptive texts, identified textual evidence before answering questions, and participated enthusiastically throughout the learning process. Furthermore, vocabulary reflection activities enabled students to identify unfamiliar words independently and strengthened their vocabulary development. The study concludes that integrating Kahoot!-based close reading with vocabulary reflection creates a more engaging, interactive, and student-centered learning environment that supports reading comprehension, vocabulary acquisition, and digital literacy development in elementary English classrooms..